Morocco's coastal aquifers: Recent observations, evolution and perspectives towards sustainability. (15th January 2022) - Ez-zaouy, Yassine; Bouchaou, Lhoussaine; Saad, Aicha; Hssaisoune, Mohammed; Brouziyne, Youssef; Dhiba, Driss; Chehbouni, Abdelghani
Abstract: During the last decades, the coastal areas of Morocco have witnessed an intense socioeconomic development associated with a continuous population growth and urban extension. This has led to an overexploitation of coastal aquifers leading to a degradation of their water quality. In order to obtain large scale overview on the quality status of Morocco's coastal aquifers (MCA) to assist national water managers to make informed decisions, a comprehensive scrutinization of the MCA against common indicators and using unified methods is essential. In this study, databases from thirteen MCA were analyzed, using multivariate statistical approaches and graphical methods in order to investigate the degree of mineralization in each aquifer and to identify the main salinization processes prevailing in groundwater. The results showed that the dominant groundwater types are Na–Cl, Ca–Mg–Cl, Ca–Mg–SO4, Ca–Mg–HCO3 and Ca–HCO3 –Cl. The Gibbs diagram and the seawater contribution (0–37%) indicate that the mineralization is mainly due to the seawater intrusion and water-rock interaction. The salinity degree diagram illustrates that almost all groundwater samples are located in the moderate to very saline zone, indicating that MCA are recharged by water from variable sources. The groundwater quality assessment shows a deterioration, particularly by seawater intrusion and significant nitrate pollution. The temporal evolution confirm that the MCA are influenced by seawater namely in the Atlantic part. The Wilcox and USSL diagram indicate that the majority of sampled water are unsuitable for irrigation uses. In addition, and by referring to the WHO and the Moroccan standards for water potability, large number of samples from the groundwaters of the MCA is not fully adequate for drinking purposes. A set of management actions (e, g., artificial recharge) are proposed in order to mitigate the effect of groundwater overexploitation and seawater intrusion to ensure the sustainability of MCA. Graphical abstract: Image 1 Highlights: Both seawater intrusion and water rock interaction are the main salinity process in MCA. A set of management actions, are proposed in order to preserve MCA.